Research of unsaturated strength characteristics for root–soil composite under different water content conditions - Xiaochan Wang; Shijie Liu; Hengxing Lan; Weifeng Sun; Xuanchen Ren; Zhouchen Li (Scientific Reports)
Abstract Plant roots are important in ecological slope protection and reinforcement, significantly affecting soil’s water-holding characteristics and shear strength. The typical herb Festuca Arundinacea root-loess composite in the Loess Plateau was taken as the research object in this paper. The matrix suction test, unsaturated shear strength test, nuclear magnetic resonance (NMR) test, and scanning electron microscope (SEM) test were used to systematically study the root–soil composite’s suction state and strength characteristics under different water content conditions and reveal its internal physical mechanism. The main research results are as follows: (i) The incorporation of roots can increase the air entry value (AEV), reduce the residual water content, and significantly enhance the matrix suction within a specific water content range, thereby increasing the unsaturated shear strength and the enhancement effect of shear strength gradually decreases with the increase of water content. (ii) The microscopic test results show that the root system accelerates the water loss of the soil under low suction conditions by changing the pore structure, increasing the total porosity and the proportion of medium and large pores. At the same time, the increase of tiny pores enhances the capillary action, increasing matrix suction. (iii) Roots can also improve the soil stress state, enhance the adsorption strength of matrix suction, and effectively improve soil shear strength. The results of this study are helpful to understanding the evolution mechanism of unsaturated strength characteristics of root–soil composite and provide the experimental basis and theoretical reference for vegetation slope protection engineering in the loess area.